1988
DOI: 10.1002/bit.260320809
|View full text |Cite
|
Sign up to set email alerts
|

Serum‐free media in hybridoma culture and monoclonal antibody production

Abstract: The replacement of serum in hybridoma cultures is considered. The focus is on the effects of serum-free media on hybridoma growth and monoclonal antibody secretion. Comparative literature data with serum supplemented cultures are discussed with an analysis of serum-free formulations and selection rules for the serum-free ingredients. In general, serum-free media which are "lipid rich" can sustain cell growth rates approaching that of serum supplemented cultures. Specific antibody secretion rate, however, is us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(32 citation statements)
references
References 62 publications
0
32
0
Order By: Relevance
“…Strategies to enhance MAB yield have extensively involved medium formulation (Glacken et al, 1988;Glassy et al, 1988;Merten and Litwin, 1991;Reuveny et al, 1985;Velez et al, 1986), modes of cell propagation (Altshuler et al, 1986;Boraston et al, 1984;Fazekas de St. Groth, 1983;Reuveny et al, 1986), and the design of high performance reactor configurations (Altshuler et al, 1986;Arathoon and Birch, 1986;Brunt, 1986;Hu et al, 1985;Posillico, 1986). Most of these procedures have focused on demonstrating the feasibility of the process (Leno et al, 1992a).…”
Section: Introductionmentioning
confidence: 97%
“…Strategies to enhance MAB yield have extensively involved medium formulation (Glacken et al, 1988;Glassy et al, 1988;Merten and Litwin, 1991;Reuveny et al, 1985;Velez et al, 1986), modes of cell propagation (Altshuler et al, 1986;Boraston et al, 1984;Fazekas de St. Groth, 1983;Reuveny et al, 1986), and the design of high performance reactor configurations (Altshuler et al, 1986;Arathoon and Birch, 1986;Brunt, 1986;Hu et al, 1985;Posillico, 1986). Most of these procedures have focused on demonstrating the feasibility of the process (Leno et al, 1992a).…”
Section: Introductionmentioning
confidence: 97%
“…This highly complex and poorly defined fluid includes growth factors, vitamins, trace elements, hormones, binding proteins and attachment factors (Barnes 1987;Glassy et al 1988). The complexity, limited availability and high cost of fetal bovine serum also presents its greatest drawbacks.…”
Section: Introductionmentioning
confidence: 99%
“…Merten et aL, (1985) found that cultivating cells below 3 7 resulted in higher titres of monoclonal antibody because the cells remained viable for longer while Reuveny et al, (1986) observed an increase in cell viability but a decrease in monoclonal antibody production rate. It has been generally observed that the growth rate of hybridomas in serum-free media is lower than in serum-supplemented media while the specific rate of monoclonal antibody secretion is higher (Glassy et al, 1988). Therefore, hybridomas are more efficient in terms of monoclonal antibody production but less efficient in terms of growth under serum-free…”
Section: Growth-dissociated Monoclonal Antibody Productionmentioning
confidence: 99%